Tetradecanoylphorbol-13-acetate (TPA) significantly increases AAV2/5 transduction of human neuronal cells in vitro. - You, Q; Brown, L; McClements, M; Hankins, M; Maclaren, R (2012)
Recombinant adeno-associated virus type 2 (AAV2) vectors have shown great promise in current ophthalmology clinical trials targeting gene delivery to the retinal pigment epithelium (RPE). To treat the majority of retinal diseases, however, gene delivery would need to be targeted to photoreceptor neurons of the outer retina. AAV2 pseudotyped with the AAV5 capsid (AAV2/5) has shown far greater transduction efficiency in photoreceptors compared to standard AAV2 vectors. For clinical trial applications using gene therapy, it is helpful to generate pre-clinical data in human cells wherever possible. There is however very little data, indeed some controversy, as to whether AAV2/5 can be used effectively in differentiated neurons in culture. In this study we show that transduction of the human neuroblastoma cell line SH-SY5Y with recombinant AAV2/5 expressing GFP is well tolerated. Furthermore, we explore the mechanism whereby exposure to retinoic acid (RA) and the phorbol ester 12-O-Tetradecanoylphorbol-13- acetate (TPA) can induce this cell line to differentiate into a stable population of human neurons, with significantly increased levels of AAV2/5 transduction. These observations may be helpful for assessing AAV2/5 vectors in vitro, particularly where it is necessary to generate pre-clinical data for clinical trials of gene therapy to the human central nervous system.